RASPBERRY PI SEBAGAI STORAGE VERSION CONTROL SYSTEM TUGAS MAHASISWA POLITEKNIK NEGERI MALANG - Rifki Hari Romadhon; Nugroho Suharto; Aad Hariyadi (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2021)
File transfer technology is now beginning to develop rapidly, many researchers have begun to develop file transfer methods, now file transfer is present in daily life in various ways. For example, in human life there are many more uses of flash memory for the process of moving files. This makes it risky to get a virus from another computer or laptop that results in file loss. In this study, we are developing a file transfer that can simultaneously manage the user to apply file version control so that the file is still written to the repository and has its own version of each uploaded file. It is hoped that implementing a version control system will help students keep all files in the repository they are working on and make changes to each file. It is expected that this study will help provide an alternative to assessment by each faculty member and may speed up and facilitate decisions related to student assessment at Malang State Polytechnic Institute. The results of this study show that the file transfer QoS on the polynema network has a packet loss value of 0%, latency of 0.672ms (download) and 0.447ms (upload), and a throughput of 330 kbps (download), 544.50 (upload)